Evaluation of serum Manganese and Zinc in non-cancerous thyroid disorders in Khartoum State-Sudan - Saeed, Abdelwahab Abdien; Ataitalla, Hoyam Abdalla; Elmukashfi, Salman Taha Ahmed (Journal of Drug Delivery and Therapeutics, 2019)
Background: The thyroid gland is responsible for the production of two hormones. Those are regulating body metabolism, neurologic development, and numerous other body functions. So this study aimed to determine the level of serum Zinc and Manganese in Sudanese patient with non-cancerous thyroid disorders in Khartoum state. Material and Methods: This study was designed as case control, which includes 100 blood samples, a 60 from these samples were collected from patient with non-cancerous thyroid disorders and 40 samples were collected from health individual as control group. A total of 60 blood samples from the patients the males is 32 sample 53% and females is 28 sample 47%. Carried out in different Hospital in Khartoum state and the sample is collected by using sterile disposable syringes and separated by centrifuge, during period from March to June 2018. And the serum levels of zinc and manganese determined by atomic absorption spectrophotometer (OPERATOR’S MANUAL January 2003 VER 3.94 C), and the obtained results were analyzed by SPSS. Results: The study showed that there was significant different because the mean of serum Zn was 0.285 in test group and 0.720 in control group with p.value of 0.001 in serum level of Zn and Mn in patient compared to control subject, significant decrease in the serum levels of Zn and increase in Mn. Mean of Mn in test group was 0.428 and 0.406 control group with p.value of 0.006. Also the study showed the age, gender of the patient and duration of the disease have no effect on the serum level of Zn and Mn. Conclusion: This study conclude that the serum level of Zn is decrease and Mn is increase in patients with non-cancerous thyroid disorders and the age, gender of the patient and duration of the disease have no effect on the serum level of Zn and Mn. Keywords: Thyroid disorders, Zinc, Manganese, Sudanese